2022
DOI: 10.3390/life12020244
|View full text |Cite
|
Sign up to set email alerts
|

In Patients with Severe COVID-19, the Profound Decrease in the Peripheral Blood T-Cell Subsets Is Correlated with an Increase of QuantiFERON-TB Gold Plus Indeterminate Rates and Reflecting a Reduced Interferon-Gamma Production

Abstract: Increased rates of indeterminate QuantiFERON-TB Gold Plus Assay (QFT-Plus) were demonstrated in patients hospitalized with Coronavirus Disease (COVID)-19. We aimed to define the prevalence and characteristics of hospitalized COVID-19 patients with indeterminate QFT-Plus. A retrospective study was performed including hospitalized COVID-19 patients, stratified in survivors and non-survivors, non-severe and severe according to the maximal oxygen supply required. Statistical analysis was performed using JASP ver0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 40 publications
1
44
0
1
Order By: Relevance
“…Ward et al reported that COVID-19 patients with both indeterminate and determinate QFT-P results were lymphopenic, although only subjects in the first group failed to produce an effective IFN-γ response after stimulation ( 1 ). Prior work performed by our group confirmed the results observed by Ward et al and provided evidence that T-lymphocyte reduction in the peripheral blood was correlated with the impairment of IFN-γ production upon phytohemagglutinin (mitogen) stimulation in the QFT-P assay and that this was leading to indeterminate results ( 6 ). Our longitudinal series shows that once the acute phase of COVID-19 is resolved, inflammatory markers and peripheral blood leukocyte counts tend to normalize, and effective interferon gamma production by T-lymphocytes is restored after both specific (mycobacterial peptide) and nonspecific (mitogen) stimulation.…”
Section: Lettersupporting
confidence: 80%
See 2 more Smart Citations
“…Ward et al reported that COVID-19 patients with both indeterminate and determinate QFT-P results were lymphopenic, although only subjects in the first group failed to produce an effective IFN-γ response after stimulation ( 1 ). Prior work performed by our group confirmed the results observed by Ward et al and provided evidence that T-lymphocyte reduction in the peripheral blood was correlated with the impairment of IFN-γ production upon phytohemagglutinin (mitogen) stimulation in the QFT-P assay and that this was leading to indeterminate results ( 6 ). Our longitudinal series shows that once the acute phase of COVID-19 is resolved, inflammatory markers and peripheral blood leukocyte counts tend to normalize, and effective interferon gamma production by T-lymphocytes is restored after both specific (mycobacterial peptide) and nonspecific (mitogen) stimulation.…”
Section: Lettersupporting
confidence: 80%
“…In a previous study conducted by our group, we found an increased rate of indeterminate results at the QFT-P assay (22.1%) in COVID-19 hospitalized patients ( 6 ) compared to the rates observed in non-COVID-19 patients from the available literature (3.2%) ( 10 ) and from our previous experience in different settings (4.3% of results were indeterminate in hematopoietic stem cell transplant recipients from January 2015 to December 2019, unpublished data).…”
Section: Lettermentioning
confidence: 78%
See 1 more Smart Citation
“…11,12,[17][18][19][20]25 An indeterminate result was defined according to the manufacturers' definition in six studies, 11,12,17,18,22,25 and as (Nil [baseline] >8.0 IU/mL) or [nil ≤8.0 IU/mL and mitogen-nil <0.5 IU/ mL] in two studies. 19,20 The term "low response to the mitogen" was used in two other studies. 10,24 Palacios-Gutiérrez et al defined "a low IFN-ɣ response to PHA" as an IFN-ɣ concentration ≥0.5 IU/mL and less than 50% below the average values and "a very low IFN-ɣ response to PHA" for an IFN-ɣ concentration <0.5 IU/mL in the mitogen tube without mentioning the term "indeterminate."…”
Section: Definition Of Indeterminate Results Of Igrasmentioning
confidence: 99%
“…Major symptoms include fever, continuous cough, shortness of breath, diarrhea, and fatigue [4]. Abnormalities in the blood of COVID-19 patients include altered levels of the peripheral blood T, B-cell subsets, and serum in ammatory parameters [5]. These alterations may indicate different stages of COVID-19 infection and predict the prognosis of patients [6].…”
Section: Introductionmentioning
confidence: 99%